Kaposi's Sarcoma-Associated Herpesvirus-Related Solid Lymphoma Involving the Heart and Brain - Jason R. Andrews; Yoon Andrew Cho-Park; Judith Ferry; Jeremy S. Abramson; Gregory K. Robbins (AIDS Research and Treatment)
Since its discovery in 1994, Kaposi's sarcoma-associated herpesvirus (KSHV) has been associated with lymphoproliferative disorders, particularly in patients infected with human immunodeficiency virus (HIV). The disorders most strongly linked to KSHV are multicentric Castleman's Disease (MCD), primary effusion lymphoma, and diffuse large B-cell lymphomas. We report an unusual case of KSHV-associated lymphoma in an HIV-infected patient manifesting with myocardial and central nervous system involvement. We discuss this case in the context of increasing array of KSHV-associated lymphomas. In the HIV-infected patient with a mass lesion, a history of cutaneous Kaposi's sarcoma and prolonged immunosuppression should alert clinicians as to the possibility of KSHV-associated lymphoproliferative disorders, in order to establish a timely diagnosis.